2020
DOI: 10.1097/aog.0000000000004013
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic Origins of Brachial Plexus Injury

Abstract: Personal or nonessential information may be redacted at the editor's discretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
2
10
0
1
Order By: Relevance
“…The incidence of BPP among the neonates of diabetic women was similar (T1D: 2.2% of vaginal live births, GDM: 0.6% of vaginal live births), 7,11 and the total incidence of BPP was higher than previously described in the literature (0.11% to 0.16% of vaginal births). 2,23 ShD was the strongest risk factor associated with injury in all neonates irrespective of the diabetes status of the parturient, which is in line with the findings of previous studies. 6,22 Furthermore, the incidence of ShD was similar to that previously reported.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The incidence of BPP among the neonates of diabetic women was similar (T1D: 2.2% of vaginal live births, GDM: 0.6% of vaginal live births), 7,11 and the total incidence of BPP was higher than previously described in the literature (0.11% to 0.16% of vaginal births). 2,23 ShD was the strongest risk factor associated with injury in all neonates irrespective of the diabetes status of the parturient, which is in line with the findings of previous studies. 6,22 Furthermore, the incidence of ShD was similar to that previously reported.…”
Section: Discussionsupporting
confidence: 91%
“…Perhaps because of the low incidences of ShD and LGA, the injuries among the neonates of non‐diabetic women occurred less often concomitant with ShD or LGA than injuries associated with maternal diabetes. A similar relationship was also reported by Johnson et al 23 …”
Section: Discussionsupporting
confidence: 90%
“…The 7-year retrospective cohort study of NBPP found that, while the overall incidence is rare at the study institution (0.08%), the frequency of NBPP with shoulder dystocia versus NBPP without shoulder dystocia, and that of transient versus persistent NBPP, did not differ significantly over the time period of the study. Moreover, the low occurrence of NBPP did not further decrease over time, regardless of Taylor & Prout, 1907) the amount of clinician experience, training, or practice with simulation (Johnson et al, 2020).…”
Section: Nbpp With and Without Shoulder Dystocia From A Comparative And Evolutionary Perspectivementioning
confidence: 82%
“…Moreover, NBPP can be the end-result of shoulder dystocia. Even without shoulder dystocia, NBPP is known to occur (Backe et al, 2008;Gherman et al, 1999;Gurewitsch et al, 2006;Johnson et al, 2020;Torki et al, 2012); a recent retrospective cohort study of NBPP injury over a 7-year period found that of the 33 NBPP cases identified, 42% did not involve shoulder dystocia (Johnson et al, 2020). We propose that a potential risk factor for NBPP without shoulder dystocia results from the human neonate simply having to follow the tortuous course through the birth canal.…”
Section: Nbpp With and Without Shoulder Dystocia From A Comparative And Evolutionary Perspectivementioning
confidence: 84%
“…Brachial plexus injuries can occur as a result of the force exerted by the delivery doctor in an attempt to resolve shoulder dystocia. Many reports of transient or persistent brachial plexus injury, including nerve root avulsions, occur both in vaginal delivery without shoulder dystocia and caesarean section [30], [31], [32].…”
Section: Definition and Pathophysiologymentioning
confidence: 99%